2003
DOI: 10.1166/jnn.2003.180
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic Conduction in Multiwalled Carbon Nanotubes

Abstract: The electrical transport in multiwalled carbon nanotubes is shown to be ballistic at room temperature with mean free paths on the order of tens of microns. The measurements are performed both in air and in the transmission electron microscope by contacting the free end of a nanotube pointing out of a fiber to a liquid metal and measuring the dependence of the nanotube resistance between the contacts. For a specific representative nanotube the resistance per unit length is found to be Rt = 31 +/- 61 omega/micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 58 publications
(169 reference statements)
0
18
0
2
Order By: Relevance
“…Due to their high degree of electron delocalization and high aspect ratio, electrons can exhibit ballistic conduction. 10 Carbon nanotubes that have been modified by photosensitive molecules have been studied with increasing frequency due to their application in optoelectronic devices. [11][12][13][14][15][16][17][18] In most cases it is the same Grätzel cell design but with CNTs mixed in with the TiO 2 to modify their electrical properties, such as decreased resistivity within the TiO 2 layer leading to a markedly increased photocurrent ͑J sc ͒ but a slightly decreased fill factor ͑ff͒ and voltage ͑V oc ͒.…”
mentioning
confidence: 99%
“…Due to their high degree of electron delocalization and high aspect ratio, electrons can exhibit ballistic conduction. 10 Carbon nanotubes that have been modified by photosensitive molecules have been studied with increasing frequency due to their application in optoelectronic devices. [11][12][13][14][15][16][17][18] In most cases it is the same Grätzel cell design but with CNTs mixed in with the TiO 2 to modify their electrical properties, such as decreased resistivity within the TiO 2 layer leading to a markedly increased photocurrent ͑J sc ͒ but a slightly decreased fill factor ͑ff͒ and voltage ͑V oc ͒.…”
mentioning
confidence: 99%
“…This superior conducting behavior resembles the ballistic transport observed in one-dimensional, nanometer-scale channels, such as quantum wires [6], carbon nanotubes [7,8] and GaAs-AlGaAs [9] at low temperature, in the form of quantum interference associated with coherence. The ballistic electron transport effect is promising for future electron devices and electric power applications such as lower supply voltage and leading to low power consumption.…”
Section: Introductionmentioning
confidence: 69%
“…The chaotic motion in the reflection component S 11 (n) is stagnant around the narrow torus for a superlattice with a cluster size of 0.55 nm and a boundary distance of 0.23 nm, rather than exhibiting global chaos in a strong electric field, showing macroscopic resonant tunneling is prevalent and produces an ensemble of electrons through multi-barriers. Berger et al [30] have reported that the mean free path for ballistic electron transport through multiwalled carbon nanotubes is of the order of tens of microns and several orders of magnitude greater than that for metals at room temperature. Thus we can assume that the increase in degree of amorphousness helps uniformity of cluster morphology, resulting in enhancement of superior ballistic transport.…”
Section: Discussionmentioning
confidence: 99%